Bifidobacterium breve UCC2003 metabolises the human milk oligosaccharides lacto-N-tetraose and lacto-N-neo-tetraose through overlapping, yet distinct pathways - James, Kieran (Sci Rep, 2016)
In this study, we demonstrate that the prototype B. breve strain UCC2003 possesses specific metabolic pathways for the utilisation of lacto-N-tetraose (LNT) and lacto-N-neotetraose (LNnT), which represent the central moieties of Type I and Type II human milk oligosaccharides (HMOs), respectively. Using a combination of experimental approaches, the enzymatic machinery involved in the metabolism of LNT and LNnT was identified and characterised. Homologs of the key genetic loci involved in the utilisation of these HMO substrates were identified in B. breve, B. bifidum, B. longum subsp. infantis and B. longum subsp. longum using bioinformatic analyses, and were shown to be variably present among other members of the Bifidobacterium genus, with a distinct pattern of conservation among human-associated bifidobacterial species.